Translational Research in Pancreatic Cancer - Strimpakos, Alexios S; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
The high mortality rate of pancreatic cancer places this uncommon malignancy quite high as a cause of cancer related deaths. Compared to other solid tumors, there is a lag in the development of new effective drugs and the actual clinical benefit remains poor over the last decade or so. The lack of therapeutic options necessitates the invention of the important molecules playing role in pancreatic carcinogenesis and the development of specific targeted therapies. Treatment advances have to be proven first in the bench before applying them at the bedside, thus why translational research is so needed. At the 2011 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium, preclinical evidence was presented regarding the efficacy of C4 compound against focal adhesion kinase (FAK) (Abstract #214), the role of the cyclooxygenase-2 (COX-2) inhibitor apricoxib in enhancing the efficacy of gemcitabine and erlotinib (Abstract #227) and the role of curcumin and ABT-888 (a poly-ADP ribose polymerase (PARP) inhibitor) as potent radiosensitizers (Abstracts #222 and #203). Interestingly, the invention of a novel monoclonal antibody (ensituximab) against the mucin epitope NPC-1Cin pancreatic and colon cancer cell lines exhibited notable antibody-dependent cellular cytotoxicity (Abstract #235). Finally, enhanced selective targeting of pancreatic tumors was achieved by combining antibody-drug conjugates (ADC) with radioimmunotherapy (Abstract #206). Image: Sotiria General Hospital. Athens, Greece.